Significance of the EU funds in regional development on the example of NUTS-3 units in Poland - Spychała, Joanna; Spychała, Marcin (Research Papers in Economics and Finance, 2021)
Within the EU cohesion policy, better and worse developed regions are subcategorised, taking account of the GDP value per capita. Based on that, areas qualifying for obtaining support from aid programs from the EU budget are established. The purpose of the article is an attempt at specifying the co-dependencies between the EU fund absorption and the changes in the level of the socio-economic development in the regional dimension. The research was conducted at the level of 73 NUTS-3 units in Poland in three stages. At the first one, the level of the development of the subregions in Poland is exhibited, subcategorising the factors of that development: human capital, material capital, natural environment as well as entrepreneurship and innovativeness. At the second stage, variation in the EU fund absorption in the researched units is presented. At the third stage, interdependencies between the extent of the absorption and the changes in the level of development within the arrangement of the factors of that development are taken up.